2020
DOI: 10.3386/w27629
|View full text |Cite
|
Sign up to set email alerts
|

Small Business Survival Capabilities and Policy Effectiveness: Evidence from Oakland

Abstract: We extend our thanks to the staff of the City of Oakland, whose foresight in implementing the survey used in this paper and their countless hours of work on it are a testament to the desire to support the people and small businesses of Oakland. Particular thanks go to Marisa Raya. We also want to thank the SafeGraph and HomeBase companies who have generously shared their data to for research related to COVID-19's impact on U.S. businesses. Finally, we thank Annette Vissing-Jorgensen for feedback and the Berkel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Spring and summer were marked by a flatter pandemic curve, gradual reopenings of state economies, and the operation of the federal Paycheck Protection Program. 11 , 12 , 13 , 14 In contrast, fall and winter saw a resurgence in COVID-19 cases and deaths, the lifting of many state business closures, school reopenings, and termination of the federal Paycheck Protection Program. Second, the survey instrument changed between the 2 periods, with a nearly month-long gap between them, a shift from weekly to biweekly frequency, and, while the health insurance questions were asked in the same way, they appeared later in the questionnaire, resulting in higher nonresponse rates (eTable 2 in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…Spring and summer were marked by a flatter pandemic curve, gradual reopenings of state economies, and the operation of the federal Paycheck Protection Program. 11 , 12 , 13 , 14 In contrast, fall and winter saw a resurgence in COVID-19 cases and deaths, the lifting of many state business closures, school reopenings, and termination of the federal Paycheck Protection Program. Second, the survey instrument changed between the 2 periods, with a nearly month-long gap between them, a shift from weekly to biweekly frequency, and, while the health insurance questions were asked in the same way, they appeared later in the questionnaire, resulting in higher nonresponse rates (eTable 2 in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast with other studies that generally aggregate small businesses into one category, Bartlett and Morse (2020) use data from Oakland, California to appraise whether the ability of small businesses to survive the pandemic depends firm size. They find that a low‐cost structure helps non‐employer businesses survive amidst substantial declines in store foot traffic and that revenue resiliency aids businesses with 1–5 employees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Granja et al (2020) found that the government support program, Payroll Protection Program (PPP), does not affect SME firm survival in the US. In contrast, Bartlett and Morse (2020) found the reverse in the medium term, where the effect is limited to microbusinesses. Wang et al (2020) found that small businesses may face financial, physical and technological barriers to accessing the bankruptcy system in the US during the pandemic.…”
Section: Literature Review Hypothesis Development and Datasetmentioning
confidence: 82%
“…While the current literature on COVID-19 has expanded rapidly, very few studies examine the effect of COVID-19 on firm survival (Alhawal et al, 2020; Bartlett & Morse, 2020; Calabrese et al, 2021; Clampit et al, 2022; Corredera-Catalán et al, 2021; Cowling et al, 2020; Gourinchas et al, 2020, 2021; Granja et al, 2020; Kells, 2020; Kuchakov & Skougarevskiy, 2021; Nurunnabi, 2020; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%